Fanconi's anemia and malignancies - Blanche P. Alter (1996)
Patients with Fanconi's anemia (FA) are at a high risk for development of malignancies. It is well-known that leukemia occurs in ∼10% of cases, with increasing risk with age. Less commonly recognized is the risk for myelodysplastic syndromes (∼5%); the relationship between myelodysplasia and evolution to leukemia remains speculative. What also needs to be emphasized is that older patients have an ever-increasing risk for development of solid tumors, with at least 5% reported to have liver tumors (male:female ratio, 2:1) and an equal number of other cancers (female:male ratio, 3:1, even after exclusion of gynecologic malignancies). Hematologists have tended to focus on aplastic anemia and leukemia. As FA patients live longer, more of the other malignancies will occur, perhaps related to cord blood or bone marrow transplant, or treatment with cytokines. This review identifies the types of tumors for which patients with Fanconi's anemia are at risk. © 1996 Wiley-Liss, Inc.